Magnetic hysteresis theory :application perspective - Arshad, Atika; Tasnim, Rumana; Khan, Sheroz; Alam, A. H. M. Zahirul (IIUM Press, 2011)

(untitled)
Magnetic materials are generally categorized into two categories, soft or hard. Soft magnetic materials are characterized by large permeability and very small coercivities while the hard one are frequently used in permanent magnet applications and are characterized by large saturation magnetizations and large coercivities. Soft and hard magnetic materials have been' introduced in many applications over last few years. Applications utilizing soft/hard magnetic materials offer both economical benefits and design flexibility. A wide range of magnetic performance requirements can be met via hysteresis loop through the proper choice of materials and the appropriate processing of those materials